Intelligence Report on the Ngie Clan by Mr. R. J. Hook D. O. (Map) Bamenda Division (Colonial Letters and the Contact of Knowledges, 1933)
This file contains colonial intelligence report on the Ngie Clan by mr. R. J. Hook in Bamenda Division
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Colonial Intelligence Report; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies